2013
DOI: 10.1126/scitranslmed.3005708
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo–Directed Evolution of a New Adeno-Associated Virus for Therapeutic Outer Retinal Gene Delivery from the Vitreous

Abstract: Inherited retinal degenerative diseases are a clinically promising focus of adeno-associated virus (AAV)-mediated gene therapy. These diseases arise from pathogenic mutations in mRNA transcripts expressed in the eye's photoreceptor cells or retinal pigment epithelium (RPE), leading to cell death and structural deterioration. Because current gene delivery methods require an injurious subretinal injection to reach the photoreceptors or RPE and transduce just a fraction of the retina, they are suitable only for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
635
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 589 publications
(676 citation statements)
references
References 47 publications
9
635
1
5
Order By: Relevance
“…Several AAVs have been tested for retinal gene delivery via the intravitreal route, and some have evoked safety concerns that have not been fully addressed at this stage. 25,43 For example, a recent study suggested that the engineered AAV variant AAV2-7m8 might be more immunogenic when used at high doses via intravitreal injections. 25 Therefore, we chose AAV2 for its known safety and efficacy in targeting RGCs in NHP studies [27][28][29] and the large body of work using this vector in human clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Several AAVs have been tested for retinal gene delivery via the intravitreal route, and some have evoked safety concerns that have not been fully addressed at this stage. 25,43 For example, a recent study suggested that the engineered AAV variant AAV2-7m8 might be more immunogenic when used at high doses via intravitreal injections. 25 Therefore, we chose AAV2 for its known safety and efficacy in targeting RGCs in NHP studies [27][28][29] and the large body of work using this vector in human clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…AAV variants have thereby been obtained which, for example, better penetrate the vitreous humor to reach the retina 7 , or exhibit improved transduction of human hepatocytes 6 or keratinocytes 23 . However, libraries consisting of shuffled capsids typically expand, but do not redirect viral tropism and, in addition, do not allow directing the selection towards a particular chosen receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The latter approaches, referred here as cell entry targeting, either use adaptors possibly shielding the viral capsid from natural receptor binding and bridging between viral capsid and the chosen target receptor (non-genetic approaches) or permanently change the capsid by genetic engineering 4,5 . As of yet, genetic engineering employing DNA shuffling of capsid-encoding genes from different serotypes and directed evolution as means to select mosaic AAV capsids with novel features has demonstrated its promise as powerful strategy to improve, but not to restrict, gene delivery to a tissue of choice [5][6][7] . Similarly, efforts to redirect tropism by insertion of receptor-targeting peptides or by non-genetic targeting approaches were successful, but have so far not resulted in AAVs that do discriminate between defined cell types as specifically as, for example, antibodies or antibody mimetics can do 4,[8][9][10] .…”
mentioning
confidence: 99%
“…Other studies have used AAV vectors containing a mouse bipolar-cell-specific enhancer to target a melanopsin.mGluR6 chimera (17) or rhodopsin (6) to bipolar cells via intravitreal injection. However, there is variation in anatomy between primates and mouse models (18), and this may render the intravitreal approach less effective in humans. Virions delivered via intravitreal injection are diluted more in primates compared with mice due to the larger volume of the vitreous, reducing the concentration of vector reaching retinal cells.…”
mentioning
confidence: 99%